2013
DOI: 10.1016/j.jconrel.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Generation of hypoallergenic neoglycoconjugates for dendritic cell targeted vaccination: A novel tool for specific immunotherapy

Abstract: The incidence of allergic disorders and asthma continuously increased over the past decades, consuming a considerable proportion of the health care budget. Allergen-specific subcutaneous immunotherapy represents the only intervention treating the underlying causes of type I allergies, but still suffers from unwanted side effects and low compliance. There is an urgent need for novel approaches improving safety and efficacy of this therapy. In the present study we investigated carbohydrate-mediated targeting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 46 publications
2
49
0
Order By: Relevance
“…Therefore, we speculated that the transamidation of dominant peptides might favor HLA binding of low-affinity, subdominant or cryptic, gliadin determinants with dramatic consequences for the immune outcome. This hypothesis appears to be in line with another study showing that masking B-cell epitopes by coupling carbohydrates to the protein surface made the protein hypoallergenic but still able to elicit elevated IgG titers following intradermal immunization [47]. Importantly, if primed by immunization, T cell populations specific for subdominant/cryptic epitopes were not diluted out by the preferential outgrowth of T cells directed to the dominant epitopes [48].…”
Section: Induction Of Gluten Tolerance By Antigen Manipulationsupporting
confidence: 76%
“…Therefore, we speculated that the transamidation of dominant peptides might favor HLA binding of low-affinity, subdominant or cryptic, gliadin determinants with dramatic consequences for the immune outcome. This hypothesis appears to be in line with another study showing that masking B-cell epitopes by coupling carbohydrates to the protein surface made the protein hypoallergenic but still able to elicit elevated IgG titers following intradermal immunization [47]. Importantly, if primed by immunization, T cell populations specific for subdominant/cryptic epitopes were not diluted out by the preferential outgrowth of T cells directed to the dominant epitopes [48].…”
Section: Induction Of Gluten Tolerance By Antigen Manipulationsupporting
confidence: 76%
“…Another approach to reduce allergenicity of proteins and develop hypoallergenic molecules is to utilize carbohydrates in order to mask IgE epitopes 58,59 . Moreover, carbohydrates can be applied for both, specific targeting of antigen presenting cells as well as modulating the resulting immune response [60][61][62] .…”
Section: Nanoparticles In Allergen-specific Immunotherapymentioning
confidence: 99%
“…Intradermal immunization of these neoglycoconjugates showed that antigen presenting cells of the skin can be addressed via carbohydrate-specific receptors and thereby increase the immunogenicity of the vaccine. Moreover, this approach does not induce novel IgE production, but instead triggers strong production of IgG, which can act as so-called blocking antibodies 3,59 .…”
Section: Nanoparticles In Allergen-specific Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…An extra limitation of the classical subcutaneous immunotherapy is the phobia in some patients to the needles and the risk associated with the use of needles [12]. Consequently, attempts for safer and more convenient and efficacious strategies are in search: generation of recombinant allergens which give no IgE-mediated activation, hypoallergenic glycoconjugates, new adjuvants favoring specific Th1 responses, and, moreover, different routes of application specific immunotherapy (SIT) especially sublingual, epicutaneous, and intra-lymphatic delivery of the allergen [13][14][15]. In the current review we will focus on nanoparticles (NP) as adjuvants for allergy immunotherapy.…”
Section: Immunotherapymentioning
confidence: 99%